Luxation injuries in primary teeth - A University based retrospective study - BANO, AMINA MEHRIN; GURUNATHAN, DEEPA; RENGALAKSHMI, SRI (The journal of contemporary issues in business and government, 2020)
Traumatic dental injuries (TDIs) are one of the most serious dental public health problems among children who seek emergency dental treatment. These injuries may influence further tooth growth, resulting in irreversible damage if they occur during the initial stages of development..The aim of the study was to find the prevalence of luxation injury in primary teeth in a university dental clinic in South India , Chennai . The data regarding pediatric patients treated for trauma who have visited the hospital during the study periods from june 2019 to march 2020 was retrieved from the university database, The search resulted with 15 in total of patients who underwent treatments for dental trauma to primary teeth . The age range of the patients included in this study was 3-10 years of age.Data tabulation was carried out in Excel. The data is imported and transcribed in Statistical Package for Social sciences version 16(SPSS,IBM corporation). Descriptive analysis was based on quantitative variables and frequencies for categorical variables. P less than or equal to 0.005 was considered statistically significant with a confidence interval of 95% . A higher prevalence in male(58.3%) children reporting with luxation injuries was compared to female(41.7%) children was observed. The highest prevalence of luxation injuries was subluxation 41.7%, followed by extrusive luxation 25%. It was also observed that female children took less time to report to the clinic when compared to the male children. The increased health awareness and the importance of prevention methods have essentially contributed to the decrease in the prevalence of TDIs, with an increase of subluxation injuries and a male gender prevalence